Tujuan pembangunan berkelanjutan ke-17: Kemitraan untuk mencapai tujuan dan implikasinya pada lembaga bidang pangan Indonesia (studi di Badan Pangan Nasional) - Fauzia, Assyifa; Mustafa, Annisa Fitri (Jurnal Inovasi Pangan dan Gizi, 2024)
Background: The 17th goal of sustainable development emphasizes on strengthening global partnerships encompassing human development, including food aspects. The institutional sector is the sector that supports food security. Integration and collaboration between sectors are highly necessary to ensure food security from food provision to distribution to consumers because supporting food security requires the involvement of cross-sectoral participation and is the duty and responsibility of the state involving the entire society. The National Food Agency (Bapanas) assists the Indonesian Ministry of Agriculture in managing food with the main tasks involving policy coordination, supply and price stabilization, food vulnerability, diversification of consumption, and food security. This article analyzes the systematic and integrated partnerships of Bapanas. Methods: This was done through literature review and unstructured interviews from open discussions with the Deputy of Food Vulnerability Field of Bapanas. Finding: International institutions in the global context, such as FAO, WFP, and WHO, play a crucial role in food policies, and Indonesia partners with FAO and WFP. Bapanas collaborates with various parties, including international institutions, universities, and food industry associations, and involves local partnerships, such as Food Guardians, to support consolidation programs and diversification of consumption as well as food security in Indonesia. Conclusion: Synergy between food supply, handling, and distribution sectors is needed to support food security, with the key role of institutional and sectoral coordination in governance.